THE IMPORTANCE OF DEVELOPING STUDENTS' COMMUNICATIVE COMPETENCE IN ENGLISH - Saydibragimova Yulduzkhon Obutkhonovna (Journals Park Publishing, 2023)
In this article, the importance of developing students' communicative competence in English, the use of new technologies in the English language class, and the impact of communicative teaching in English language teaching on students are fully discussed.
Keywords: English language, communicative competence, communicative teaching, interactivity.